An ethical analysis of withdrawal of therapy in patients with implantable cardiac electronic devices: Application of a novel decision algorithm. (1st November 2013) - Kay, G. Neal; Pelosi, Frank
Abstract : Patients with cardiovascular implantable electronic devices (CIEDs), which include pacemakers and implantable cardioverter-defibrillators (ICDs), may request deactivation of their devices as they approach the end of life. The Heart Rhythm Society (2010) has stated that "ethically, and legally, there are no differences between refusing CIED therapy and requesting withdrawal of CIED therapy." On the basis of the principle that there is no ethical distinction between withholding and withdrawing treatment, this professional organization has suggested that both the antibradycardia and antitachycardia features of these devices may be disabled at the patient's request. We argue that disabling ICD shocks is analogs to a do-not-resuscitate order and is ethically permissible whereas withdrawing pacing from a pacemaker-dependent patient is an act of intentionally hastening death and not morally licit.